DEVELOPMENT OF A METER FOR THE COMBINED FLOW THROUGH CONTRACTED SLUICE GATE AND WEIR - Ahmed, Fadhil H. (Al-Mukhtar Journal of Sciences, 1997)
The sluice gate and weir are used to control and to measure the discharge for the flow through the open channels for many years. Both of these meters have certain disadvantages, there fore a combination of these meters will remove the disadvantages concerning the floating material collection and silt deposition at the upstream. Six models were installed in a flume of 50 cm width. Eight runs were tested for each model. In the first three models, with of the meter opening (b) was changed. While in the other three models, the vertical distance (y). The results indicated that values were ranged between 1.35-1.55, and n values were ranged between 0.10-0.49. The mean discharge coefficients (CZ) were not changed significantly, they were ranged between 0.588-0.600 with a mean value of 0.595 for all models, and mean deviations were ranged between 0.29-1.08.